2020
DOI: 10.1097/bpo.0000000000001705
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of Nerve Transfers for Brachial Plexus Birth Injury: A Systematic Review

Abstract: Background: The purpose of this article is to systematically review the peer-reviewed literature on the morbidity of nerve transfers performed in patients with brachial plexus birth injury (BPBI). Nerve transfers for restoration of function in patients with BPBI that fail nonoperative management are increasing in popularity. However, relatively little attention has been paid to the morbidity of these transfers in the growing patient. The authors systematically review the current literature regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The second condition to justify sacrificing intact nerves is that limb functionality is not decreased by doing so. In this respect, the literature on reported donor nerve complications for BPBI has been summarized in a recent systematic literature review (Hinchcliff et al., 2021). At first glance, it seems that nerve transfers are safe to use, as severe complications were not noted.…”
Section: Advance or Controversy: Increased Use Of Distal Nerve Transf...mentioning
confidence: 99%
“…The second condition to justify sacrificing intact nerves is that limb functionality is not decreased by doing so. In this respect, the literature on reported donor nerve complications for BPBI has been summarized in a recent systematic literature review (Hinchcliff et al., 2021). At first glance, it seems that nerve transfers are safe to use, as severe complications were not noted.…”
Section: Advance or Controversy: Increased Use Of Distal Nerve Transf...mentioning
confidence: 99%
“…45 Unlike nerve graft reconstruction, partial cutaneous sensory recovery is not expected after distal nerve transfers of motor donors and recipients, and donor nerve morbidity with functional downgrade is always a potential risk. 53,85,86 Finally, as motor recovery following cervical root nerve grafting may not be complete until 4 years of age, it remains to be shown whether the final outcomes of distal nerve transfers are equivalent to or surpass those of nerve grafting. 87 Based on these considerations, current indications for distal nerve transfers in BPBI are outlined in Table 6.…”
Section: Distal Nerve Transfers (Neurotization)mentioning
confidence: 99%
“…Furthermore, it is rare for a study to compare multiple treatment strategies for a set of patients with a common pathology 59 . Additionally, authors frequently fail to report any donor site morbidity associated with nerve transfers in a standard fashion, although the potential effect of denervation on musculoskeletal growth is acknowledged 60 . In a report by the International Federation of Societies for Surgery of the Hand, the committee recommended that surgeons who treat BPBI be both able and willing to include brachial plexus exploration and nerve reconstruction as part of their treatment algorithm and not overly rely on nerve transfers alone 74 .…”
Section: Nerve Reconstructionmentioning
confidence: 99%
“…However, when comparing nerve reconstruction techniques performed in patients after 9 months of age, Daly et al found no difference between nerve grafting and nerve transfers 42 . Additionally, the exclusive use of nerve transfers in brachial plexus reconstruction may waste otherwise viable donor axons from intact nerve roots, is associated with potential donor site morbidity 60 , and ignores sensory innervation.…”
Section: Nerve Reconstructionmentioning
confidence: 99%